Life-cycle regulation of carbohydrate metabolism revealed by glucokinase (gck) in two cyprinids, Spinibarbus denticulatus and Schizothorax prenanti - Yongyao Guo; Yue Zhang; Tiancai Li; Longjun Deng; Zhonggang Guo; Li Liu; Pengyu Chen; Luojia Li; Wei Luo; Dongjie Wang; Zongjun Du (Aquaculture, 2026)

Study on the Bioavailability of Arsenic in the Rice–Crayfish Farming System - Kelei Zhang; Shoudong Zhang; Longjun Deng; Tiancai Li; Li Liu; Wei Luo; Yibo Zhang; Yongyao Guo; Dan Liu; Shiyong Yang; Jun Wang; Dongjie Wang; et al. (Fishes, 2025)
Rice–fishery integrated farming has expanded rapidly in China, yet its implications for arsenic (As) accumulation remain insufficiently understood. This study evaluated As bioavailability and enrichment in a rice–crayfish farming system (RCFS) by establishing controlled field plots with soil As concentrations ranging from 5 to 40 mg/kg under three water-management regimes: alternating wetting and drying (AWD), continuously flooded (CF), and RCFS. Soil–water physicochemical variables and As accumulation in both rice organs and crayfish tissues were systematically analyzed, followed by human health risk assessment. Inorganic As in brown rice increased linearly with soil As, following Y = 0.0117X + 0.0598 (R2 = 0.96), and the estimated soil safety thresholds were 26.48 mg/kg for AWD, 11.98 mg/kg for RCFS, and 9.24 mg/kg for CF. AWD consistently exhibited the lowest As risk due to its ability to elevate soil Eh and maintain a more favorable pH, thereby suppressing As mobilization. Compared with CF, RCFS reduced As bioavailability through crayfish-induced bioturbation, which increased Eh, enhanced SOM and CEC, and improved soil aeration. As accumulation in crayfish tissues also rose with soil As, with abdominal muscle As fitting Y = 0.0085X + 0.0553 (R2 = 0.8588). Although abdominal muscle met safety limits, the hepatopancreas accumulated substantially higher As and exceeded carcinogenic risk thresholds, even at 5 mg/kg of soil As, indicating a potential health concern for consumers. This work elucidates As dynamics and enrichment mechanisms in RCFS, providing guidance for safer rice–crayfish production in As-impacted areas.

A comprehensive understanding of thermal tolerance in Percocypris pingi (Tchang, 1930) under different acclimation temperatures supported by behavioral assessments - Yongyao Guo; Tong Li; Li Liu; Tiancai Li; Longjun Deng; Siyi Zhu; Shun Zhong; Qingjie Wang; Dongjie Wang; Wei Luo; Zongjun Du (Journal of Thermal Biology, 2025)

Engineering human midbrain organoid microphysiological systems to model prenatal PFOS exposure - Chunhui Tian; Hongwei Cai; Zheng Ao; Longjun Gu; Xiang Li; Vivian C. Niu; Maria Bondesson; Mingxia Gu; Ken Mackie; Feng Guo (Science of The Total Environment, 2024)

Exploring the spatial relationship between soil quality index and soil ecosystem services driven by social-ecological factors: A peri-urban case study in central China - Jiaxin Guo; Guangyu Li; Qing Zhu; Yefeng Jiang; Xi Guo; Longjun Ding; Xiaomin Zhao (CATENA, 2024)

A Novel Disturbance Stress Direction Identification Method of Rock Mass Using Acoustic Parameters - Yongchao Chen; Jiang Guo; Longjun Dong (Rock Mechanics and Rock Engineering, 2024)

Enhanced reaction kinetics and structure integrity of Cu/F co-doped SnO2@C composite for high-performance lithium-ion batteries - Shixin Huang; Longjun Guo; Wei Liu; Chunjin Hang; Rong An; Yongfeng Li; Yanhong Tian (Chemical Engineering Journal, 2024)

IFITM3 restricts porcine deltacoronavirus infection by targeting its Spike protein - Jianxiao Wu; Rongfeng Tang; Xiaorong Zhang; Mingzhe Gao; Longjun Guo; Liaoyuan Zhang; Da Shi; Xin Zhang; Hongyan Shi; Hongying Song; Li Feng; Jianfei Chen (Veterinary Microbiology, 2024)

Integrative analysis of transcriptomic profile reveals potential roles of miRNAs in regulating development of Marsupenaeus japonicas - Jing Wang; Longjun Pu; Xiaojuan Zhang; Cuicui Liang; Dandan Dong; Jiantao Guan; Huarong Guo (Journal of Oceanology and Limnology, 2024)

High temporal and spatial resolution characteristics of evaporation, transpiration, and evapotranspiration from a subalpine wetland by an advanced UAV technology - Chunhua Yan; Jiao Xiang; Longjun Qin; Bei Wang; Zhe Shi; Weiyang Xiao; Muhammad Hayat; Guo Yu Qiu (Journal of Hydrology, 2023)

Corrigendum to “Seasonal variation in water uptake patterns of two greening species and their responses to rainfall events in a subtropical megacity of China” [J. Hydrol. (2023) 129262] - Bei Wang; Chunhua Yan; Zhe Shi; Jinshan Ding; Tengran Zhang; Longjun Qin; Guo Yu Qiu (Journal of Hydrology, 2023)

An in-situ measurement and assessment of evaporative cooling effects of low impact development facilities in a subtropical city - Chunhua Yan; Junjie Ding; Bei Wang; Longjun Qin; Zhe Shi; Guo Yu Qiu (Agricultural and Forest Meteorology, 2023)

Seasonal variation in water uptake patterns of two greening species and their responses to rainfall events in a subtropical megacity of China - Bei Wang; Chunhua Yan; Zhe Shi; Jinshan Ding; Tengran Zhang; Longjun Qin; Guo Yu Qiu (Journal of Hydrology, 2023)

Assessing the variations of evapotranspiration and its environmental controls over a subalpine wetland valley in China - Jiao Xiang; Muhammad Hayat; Guo Yu Qiu; Weiyang Xiao; Xianli Xu; Peng Mao; Chunhua Yan; Longjun Qin (Journal of Hydrology, 2023)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

Computational identification and characterization of microRNAs and their targets in Penaeus monodon - Longjun Pu; Jing Wang; Yu Wang; Jianwei Zuo; Huarong Guo (Journal of Oceanology and Limnology, 2018)

Characterization of porcine epidemic diarrhea virus infectivity in human embryonic kidney cells - Jian Zhang; Longjun Guo; Yunfei Xu; Lijun Yang; Hongyan Shi; Li Feng; Yue Wang (Archives of Virology, 2017)

Production of porcine TNFα by ADAM17-mediated cleavage negatively regulates porcine reproductive and respiratory syndrome virus infection - Ren Li; Longjun Guo; Weihong Gu; Xiaolei Luo; Jian Zhang; Yunfei Xu; Zhijun Tian; Li Feng; Yue Wang (Immunologic Research, 2016)

Identification of three new type-specific antigen epitopes in the capsid protein of porcine circovirus type 1 - Liping Huang; Yuehua Lu; Yanwu Wei; Longjun Guo; Changming Liu (Archives of Virology, 2012)

Carbonate mineral saturation states along the U.S. East Coast - Li-Qing Jiang; Wei-Jun Cai; Richard A. Feely; Yongchen Wang; Xianghui Guo; Dwight K. Gledhill; Xinping Hu; Felipe Arzayus; Feizhou Chen; Justin Hartmann; Longjun Zhang (Limnology and Oceanography, 2010)
To assess the impact of ocean acidification on the carbonate chemistry of the shelf waters off the southeastern United States (South Atlantic Bight [SAB]), we measured carbonate mineral saturation states from January 2005 to May 2006. The findings reveal that aragonite (Ω arag : 2.6–4.0) and calcite (Ω cal : 4.1–6.0) saturation states were considerably higher than those recently reported along the West Coast of North America. Different water mass age between the Atlantic and Pacific Oceans during global ocean circulation is the primary reason for the higher carbonate mineral saturation states in the SAB than along the West Coast. The contrasting water temperatures in the two coasts contribute to such differences. Both upwelling and freshwater discharge also play important roles in controlling saturation state. Carbonate mineral saturation in the surface water of the West Coast is strongly controlled by the upwelling of high‐salinity, low‐temperature, low‐oxygen, and low‐pH deep water. In comparison, saturation states in the surface water of the SAB coast are rarely affected by upwelling. Instead, they are strongly influenced by the input of low‐saturation‐state water from rivers. Continued increases of atmospheric CO 2 under the Intergovernmental Panel on Climate Change B1 emission scenario will decrease the carbonate mineral saturation states by up to 40% by the end of this century, and aragonite will approach undersaturation near the coast.